User Needs of Online Tutoring Applications Using House of Quality - Qurrata Aini; Eko Ruddy Cahyadi; Faqih Udin (Jurnal Aplikasi Bisnis dan Manajemen, 2025)
Background: Technology has significantly influenced the education sector, particularly with the rise of mobile learning through online tutoring applications. However, users have reported several shortcomings, such as overly minimalist user interfaces, excessive animations, and suboptimal video and audio content quality. Additionally, data security concerns in mobile learning remain a critical issue.Purpose: This research aims to analyze the user needs of online tutoring applications as identified by users and potential users and translate these needs into actionable technical responses.Methodology: The study employs the House of Quality method and was conducted in the Jabodetabek area from 2021 to 2022. Data collection methods included voluntary and purposive sampling, using questionnaires distributed via Google Forms, as well as interviews and focus group discussions.Results: The House of Quality analysis highlights the prioritized user needs in the following order: 1) security and privacy, 2) performance, 3) information, 4) responsiveness, 5) technical reliability, and 6) design. The technical requirements identified to address these needs include network coverage, storage capacity, data transmission speed, application size, power consumption, network accessibility, and display resolution.Conclusion: The top user priorities for online tutoring applications are security and privacy, performance, and information. The most critical technical responses to meet these needs are improvements in network coverage, storage capacity, and data transmission speed.Originality/Value (State of the Art): This study translates user needs for online tutoring applications into specific technical responses, providing a foundation for the development and improvement of such applications. Keywords: online tutoring applications, mobile learning, house of quality, user needs, technical responses